PENGENDALIAN CROCIDOLOMIA PAVONANA PADA TANAMAN KUBIS SECARA TERPADU - Paat, Frangky J.; Maramis, R.T. D. (EUGENIA, 2019)
Research on the integrated control of Crocidolomia pavonana on cabbage aims to test various cabbage cultivation techniques, namely the use of organic fertilizers, botanical insecticides, and multiple croping. This research was conducted in Paslaten Sub-District, Tomohon City, from January 2011 to January 2012. The parameters observed included the percentage of attacks, cabbage production, profit analysis of organic and non- organic cultivation, measurement of climate parameters, analysis of total soil N content, total N content of fertilizer organic foliage and chicken manure. This experiment used a randomized block design (RBD) with orthogonal contrast with eleven (11) treatments and four (4) replications. The results showed that the highest attack percentage at 6 mst was found in mitraflora + B. asiatica fertilizer treatment 12.5% chicken manure + B. asiatica 7.14%, farmer habit patterns 5.36%, and campus organic fertilizer treatment + B asiatica 1.79%. The highest percentage of attacks at 8 mst was found in the treatment of mitraflora + B. asiatica fertilizer 37.5%, chicken manure + B. asiatica 26.79%, campus organic fertilizer + B. asiatica 16.07%, farmers' habit patterns 7.14%. The highest attack percentage at 10 mst was found in mitraflora + B. asiatica fertilizer treatment 21.43%, farmer habit pattern treatment 16.07%, chicken manure + B. asiatica 12.5%, campus organic fertilizer + B. asiatica 10, 71%. The highest cabbage production was produced by the treatment of farmers' habit patterns, namely 42.8 kg / plot, followed by the treatment of campus organic fertilizer + B. asiatica with a production rate of 34.6 kg / plot, treatment of chicken manure + B. asiatica 29.5 kg / plot, fertilizer treatment mitraflora + B. asiatica 27.8 kg / plot.